Correlation and Path Coefficient Analysis for Yield and Contributing Traits in Yellow Sorghum (Sorghum bicolor (L.) Moench) - Sujatha, K.; Akshay, H. V.; Maheshwaramma, S.; Rani, C. Sudha; Anuradha, Ch.; Kumar, C. V. Sameer (International Journal of Bio-resource and Stress Management, 2025)
The present study was conducted during rabi 2024–25 at Agricultural Research Station, Tandur to assess the nature of the association between grain yield and its component traits and monitor the direct and indirect effects of each of the component traits on grain yield of yellow sorghum. Fifty-two genotypes were evaluated for twelve yield contributing traits under residual soil moisture conditions in black soil. Correlation analysis indicated that fodder yield, number of grains panicle-1, number of leaves plant-1, leaf width, test weight, and panicle width had significant positive association with grain yield at both genotypic and phenotypic levels. Poor and insignificant correlation of grain yield was observed with plant height, leaf length, and panicle length. Path analysis partitioned the correlations into direct and indirect effects, providing a deep insight into trait–yield relationship. Significant positive direct effects of number of grains panicle-1, test weight, days to maturity and fodder yield and significant indirect effects of traits namely panicle width, panicle length and leaf length on grain yield confirmed that these traits should be prioritized during selection for ensuring higher genetic gain in grain yield in yellow sorghum improvement programs. The negative direct effect of days to 50% flowering and days to maturity on grain yield at the phenotypic and genotypic levels respectively implied that medium-flowering genotypes were more favourable for rabi situations.